Design Sensitivity Studies on a Hydroacoustic Projector Using an Experimentally Validated Easy-to-Build Model - SREEJITH, Vattaparambil Sreedharan; TIWARI, Nachiketa (Archives of Acoustics, 2022)
Hydroacoustic projectors are useful for generating low frequency sounds in water. Existing works on hydroacoustic projectors require two significant enhancements, especially for designers. First, we need to understand the influence of important projector design parameters on its performance. Such insights can be very useful in developing a compact and efficient projector. Second, there is a need for an integrated model of the projector based on easily available and user-friendly numerical tools which do not require development of complex customised mathematical analogs of projector components. The present work addresses both such needs. Towards these goals, an experimentally validated, easy-to-build projector model was developed and used to conduct design sensitivity studies. We show that reductions in pipe compliance and air content in oil, and an increase in orifice discharge coefficient can yield remarkable improvements in projector’s SPL. We also show that reductions in pipe length and cylinder diameter cause moderate improvements in performance in mass and stiffness controlled regions, respectively. In contrast, the projector performance is insensitive to changes in pistonic mass, cylinder length, and diaphragm stiffness. Finally, we report that while pipe compliance and air content in oil can sharply alter system resonance, the effects of changes in pipe length and pistonic mass on it are moderate in nature.